2021
DOI: 10.4000/geomorphologie.15113
|View full text |Cite
|
Sign up to set email alerts
|

Caractéristiques hydro-géomorphologiques des microhabitats d’Unio crassus (Ardenne, Belgique)

Abstract: Caractéristiques hydro-géomorphologiques des microhabitats d'Unio crassus (Ardenne, Belgique)Hydro-geomorphological characteristics of Unio crassus microhabitats (Ardenne, Belgium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
1
0
3
Order By: Relevance
“…Also widely analysed were the effect of wildfires on the increase of soil erosion (Lane et al 2006;Warrick et al 2015). Many sedimentary studies also showed the ecological impacts of sediment accumulation on stream habitats (Parkinson et al 1999;Tramblay et al 2010;Collins et al 2011); some authors associated it to a decrease of biodiversity in silt-clogged river beds (Vaessen et al 2021), while others to human impacts on sediment yield resulting in the consolidation of riverbanks or an increase of flooding risks (Dumas 2007;Vanmaercke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also widely analysed were the effect of wildfires on the increase of soil erosion (Lane et al 2006;Warrick et al 2015). Many sedimentary studies also showed the ecological impacts of sediment accumulation on stream habitats (Parkinson et al 1999;Tramblay et al 2010;Collins et al 2011); some authors associated it to a decrease of biodiversity in silt-clogged river beds (Vaessen et al 2021), while others to human impacts on sediment yield resulting in the consolidation of riverbanks or an increase of flooding risks (Dumas 2007;Vanmaercke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Des pièges à sédiments fins (Figure 2) enfouis sous la surface du lit ont été utilisés afin de quantifier l'infiltration de sédiments fins dans la sous-couche (Vaessen et al, 2021).…”
Section: Les Pièges à Sédiments Finsunclassified
“…Son cycle de vie comprend une phase parasitaire de développement sur un poisson-hôte nécessaire pour la métamorphose du stade larvaire (glochidie) en jeune moule. Elle occupe des habitats variés en termes de paramètres physico-chimiques, de vitesse de courant et de substrat (Denic et al, 2014 ;Vaessen et al, 2021). Concernant ce dernier paramètre, dans la Sûre, une préférence est observée pour les substrats gravillonneux ou sableux non colmatés qui lui permettraient de s'enfouir facilement pour s'abriter et éviter d'être emportée par les crues (Vaessen et al, 2021).…”
Section: Introductionunclassified
See 1 more Smart Citation